ANALYSIS OF IMAGERY IN THE NOVEL AKSARANITA BY BUMINYAKALA - Kasmawati, Kasmawati; Rahayu, Sri (Universitas Muhammadiyah Makassar, 2025)
Language is a mental image that aims to convey the author's thoughts and feelings in a literary work. Language in novels, which describes the author's imagination, is an interesting stylistic object to study. According to stylistic experts, there are five different types of imagery: sight, sound, movement, touch, and smell. The novel Aksaranita, written by Buminyakala, utilizes all five types of imagery. The novel tells the story of how Aksara's presence changes Saranita's view of the world, including love, before he leaves her without a word. The purpose of the research is to find out, describe, analyze, and interpret the data on the types of imagery in the novel Aksasanita by Buminyakala. This research uses a qualitative approach. Using descriptive research methods. The data collection technique used by the author is the hermeneutic technique. The data analysis technique is based on content analysis. The data validity technique uses the triangulation technique. The results of the research on image analysis in the novel Aksaranita Karya Buminyakala show that the overall image is dominated by visual imagery and motion imagery, for auditory imagery and tactile imagery are quite significant in the novel. While olfactory imagery has less data found. The five images play an important role in the novel Aksarnita Karya Buminyakala to create a picture based on the imagination of the narrator in the novel. This research enriches literary studies, especially in the field of stylistics and imagery theory, and helps understand how language shapes meaning and aesthetic experience in texts. The analysis results of this research can be utilized in the learning of literature, the development of literary criticism. Thus, image analysis not only reveals the beauty of language in novels, but also makes a real contribution to the learning of Indonesian Language and Literature.